Nalar Politik Abdurrahman Wahid (Studi Atas Pemikiran tentang NKRI dalam Perspektif Fiqh) - Johari (Menara Tebuireng, 2018)
Dissent regarding the relationship between religion and the state is a fundamental problem that continues to advance in the history of Muslim travel and is at the center of the attention of Islamic movements in the world, including Indonesia. Abdurrahman Wahid has a clear view of the Unitary Republic of Indonesia, which does not approve the establishment of an Indonesian Islamic State and accepts the NKRI based on Pancasila. His thinking has a strong foothold in Islamic law. His rejection of the establishment of an Indonesian Islamic State, and his acceptance of the concept of the nation state, in addition to affirming his approach which tended to be substantive, realistic inclusive was also built on fiqh arguments. The arguments are; firstly form of state including something ijtiha>di, secondly prioritize goals (al-maqa>s}id) rather than Intermediaries (al-wasa>'il), and thirdly consider the social and historical context of society.